PENGEMBANGAN MEDIA AUDIO–VISUAL BERBASIS PROBLEM BASED LEARNING PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SDN 02 PASAR BARU PESISIR SELATAN - Ikhwan, Khairul; Kamala Dola, Cici (LP2M Universitas Adzkia, 2024)
This study aims to develop and validate instructional media based on the Problem-Based Learning (PBL) model for integrated thematic learning, theme 3, sub-theme 2. The background of the study is that the media used in schools has not yet implemented a learning model, only presenting content and assignments without adequate illustrations, with unappealing visuals and printed on easily torn newspaper paper. This research is a type of Research and Development (R&D) using the 4-D model (Define, Design, Develop, Disseminate). The results show that the developed media received highly valid scores from experts: design (93.75%), content (90%), language (83.25%), and lesson plan (87.5%). The PBL-based media is declared highly valid and suitable for use. The implementation of the PBL model in the media stimulates students’ creative thinking skills and fosters their learning interest through a more active, contextual, and engaging learning process